2009
DOI: 10.1038/nrmicro2109
|View full text |Cite
|
Sign up to set email alerts
|

Principles of c-di-GMP signalling in bacteria

Abstract: On the stage of bacterial signal transduction and regulation, bis-(3'-5')-cyclic dimeric guanosine monophosphate (c-di-GMP) has long played the part of Sleeping Beauty. c-di-GMP was first described in 1987, but only recently was it recognized that the enzymes that 'make and break' it are not only ubiquitous in the bacterial world, but are found in many species in huge numbers. As a key player in the decision between the motile planktonic and sedentary biofilm-associated bacterial 'lifestyles', c-di-GMP binds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
1,559
1
42

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,355 publications
(1,625 citation statements)
references
References 113 publications
23
1,559
1
42
Order By: Relevance
“…cheOp1 homologues belong to the well-conserved F5 class of chemotaxis systems 21 , so far almost exclusively found among alphaproteobacteria, whereas cheOp2 and cheOp3 homologues belong to the ACF class 21 . All operons encode the canonical set of chemotaxis genes cheA, cheW, cheY, cheB and cheR (although cheOp2 only has a hybrid cheY homologue) plus additional che homologues and putative chemotaxis-related genes encoding MCP, ParA-like 22 , EAL or GGDEF 23 domain proteins in cheOp2-4. The best hits are to orthologues from other magnetotactic alphaproteobacteria (Supplementary Table 2) followed by P. molischianum and different Rhodospirillum and Azospirillum species.…”
Section: Resultsmentioning
confidence: 99%
“…cheOp1 homologues belong to the well-conserved F5 class of chemotaxis systems 21 , so far almost exclusively found among alphaproteobacteria, whereas cheOp2 and cheOp3 homologues belong to the ACF class 21 . All operons encode the canonical set of chemotaxis genes cheA, cheW, cheY, cheB and cheR (although cheOp2 only has a hybrid cheY homologue) plus additional che homologues and putative chemotaxis-related genes encoding MCP, ParA-like 22 , EAL or GGDEF 23 domain proteins in cheOp2-4. The best hits are to orthologues from other magnetotactic alphaproteobacteria (Supplementary Table 2) followed by P. molischianum and different Rhodospirillum and Azospirillum species.…”
Section: Resultsmentioning
confidence: 99%
“…Many c-di-GMP-binding proteins playing a role in attachment harbor PilZ, FleQ, PelD, and PleD domains (reviewed in reference 58). PilZ domains have been discovered in sequences of polysacchariderelated proteins, including bacterial cellulose synthases and alginate biosynthesis protein Alg44, as well as proteins involved in flagellar motility, including the enterobacterial YcgR and firmicute YpfA protein families (58). In E. coli, the c-di-GMP receptor YcgR has been shown to bind to the FliG subunit of the flagellum switch complex, with high levels of c-di-GMP inducing the counterclockwise bias in E. coli flagellar rotation, resulting in smooth swimming (44).…”
Section: Modulation Of Cyclic Di-gmpmentioning
confidence: 99%
“…Since then, c-di-GMP has been discovered throughout eubacteria and found to act as a secondary messenger controlling diverse phenotypes, such as biofilm formation, virulence, motility and pathogenesis (Hengge, 2009;Mills et al, 2011;Sondermann et al, 2012;Wolfe & Visick, 2008;Yi et al, 2010). Numerous studies have shown that increases in c-di-GMP production correlate with biofilm formation and a sessile lifestyle, while reduced c-di-GMP concentrations promote motility and virulence-factor production.…”
Section: Introductionmentioning
confidence: 99%